Highly scalable discrete-particle simulations with novel coarse-graining: accessing the microscale. (18th August 2018) - Mattox, Timothy I.; Larentzos, James P.; Moore, Stan G.; Stone, Christopher P.; Ibanez, Daniel A.; Thompson, Aidan P.; Lísal, Martin; Brennan, John K.; Plimpton, Steven J.
ABSTRACT: Simulating energetic materials with complex microstructure is a grand challenge, where until recently, an inherent gap in computational capabilities had existed in modelling grain-scale effects at the microscale. We have enabled a critical capability in modelling the multiscale nature of the energy release and propagation mechanisms in advanced energetic materials by implementing, in the widely used LAMMPS molecular dynamics (MD) package, several novel coarse-graining techniques that also treat chemical reactivity. Our innovative algorithmic developments rooted within the dissipative particle dynamics framework, along with performance optimisations and application of acceleration technologies, have enabled extensions in both the length and time scales far beyond those ever realised by atomistic reactive MD simulations. In this paper, we demonstrate these advances by modelling a shockwave propagating through a microstructured material and comparing performance with the state-of-the-art in atomistic reactive MD techniques. As a result of this work, unparalleled explorations in energetic materials research are now possible. GRAPHICAL ABSTRACT: